2015
DOI: 10.1186/s12887-015-0444-2
|View full text |Cite
|
Sign up to set email alerts
|

Association of neck circumference and high blood pressure in children and adolescents: a case–control study

Abstract: BackgroundHigh blood pressure (BP) is a serious, common and growing global public health problem. The aim of this study was to evaluate the associations between high NC (neck circumference) alone and in combinations with BMI (body mass index), WC (waist circumference), and high BP among Lithuanian children and adolescents aged 12 to 15 years.MethodsAn epidemiological case–control study was performed between May 2012 and November 2013. NC, WC, hip circumference (HC), mid-upper arm circumference (MUAC), body hei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
38
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(45 citation statements)
references
References 45 publications
5
38
0
2
Order By: Relevance
“…Eventually, a total of 9 studies were included in the present review. [1826] The quality of the included articles is summarized in Table 1.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Eventually, a total of 9 studies were included in the present review. [1826] The quality of the included articles is summarized in Table 1.…”
Section: Resultsmentioning
confidence: 99%
“…[22] The prevalence of hypertension may be overestimated in these studies. Second, some new obesity indices, such as neck circumference [26] and mid-upper arm circumference, [42] had been used to screen elevated BP in children. These obesity indices were not in the meta-analysis because related research is few.…”
Section: Discussionmentioning
confidence: 99%
“…[10] Nafiu et al . have shown a significant positive association of NC and obesity with increase in BP in a cross-sectional study done in children.…”
Section: Discussionmentioning
confidence: 99%
“…Renata et al shown association of neck circumference and high blood pressure in children and adolescents. 15 Katz et al had shown that neck to waist ratio, an index of body fat distribution predicts obstructive sleep apnoea in overweight/obese children. 16 Another study conducted in 324 Greek children aged 9 -13 years found that NC was associated with most cardiovascular disease (CVD) risk factors.…”
Section: Discussionmentioning
confidence: 99%